2021
DOI: 10.29040/jiei.v7i2.2473
|View full text |Cite
|
Sign up to set email alerts
|

Pendapatan, Pendidikan, Persepsi Kemudahan, dan Sikap sebagai Mediasi terhadap Keputusan Penggunaan Mobile Banking Syari’ah

Abstract: The existence of Covid-19 which limited society to transact online has made an increment several islamic banks in users and the number of transactions. The aim of this study was to review test how the influence of income, education, and perceived ease of use through attitude against the usage decision of shari’a mobile banking. A Structural Equation Model (SEM) was used to analyze in this study with WarpPLS 7.0 approach. Respondent of this research was general public of Surabaya City. Sampling technique which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Alalwan et al, (2016) from Jordan and (V. A. in Vietnam found that intention to use M-Banking is significantly influenced by the variable. Therefore, this study proposes the following hypotheses: H1: Perceived usefulness positively and significantly impact trust H2: Perceived usefulness positively and significantly impact intention to use M-Banking Perceived Ease of Use In the M-Banking context, perceived ease of use refers to consumers' belief that M-Banking can provide practical benefits as emphasized by Riptiono et al, (2021), Singh & Srivastava, (2016) and Salmah, (2021). As a crucial construct of TAM, the variable has been extensively investigated in several studies on M-Banking acceptance (Siyal et al, 2019;Zarnadze, 2021).…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Alalwan et al, (2016) from Jordan and (V. A. in Vietnam found that intention to use M-Banking is significantly influenced by the variable. Therefore, this study proposes the following hypotheses: H1: Perceived usefulness positively and significantly impact trust H2: Perceived usefulness positively and significantly impact intention to use M-Banking Perceived Ease of Use In the M-Banking context, perceived ease of use refers to consumers' belief that M-Banking can provide practical benefits as emphasized by Riptiono et al, (2021), Singh & Srivastava, (2016) and Salmah, (2021). As a crucial construct of TAM, the variable has been extensively investigated in several studies on M-Banking acceptance (Siyal et al, 2019;Zarnadze, 2021).…”
Section: Perceived Usefulnessmentioning
confidence: 99%